2017
DOI: 10.1136/bmjdrc-2016-000283
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean style diet is associated with low risk of new-onset diabetes after renal transplantation

Abstract: ObjectiveThe incidence of new-onset diabetes after transplantation (NODAT) and premature mortality is high in renal transplant recipients (RTR). We hypothesized that a Mediterranean Style diet protects against NODAT and premature mortality in RTR.Research design and methodsA prospective cohort study of adult RTR with a functioning graft for >1 year. Dietary intake was assessed with a 177-item validated food frequency questionnaire. Patients were divided based on a 9-point Mediterranean Style Diet Score (MDS): … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 53 publications
3
47
1
Order By: Relevance
“…Dietary patterns can directly be translated into dietary recommendations to be used in clinical practice 7, 8. Previously, we found that a Mediterranean‐style diet is associated with a lower risk of new‐onset diabetes and all‐cause mortality after renal transplantation 9. In contrast to the Mediterranean diet, which is based on a diet traditionally consumed by the inhabitants of regions surrounding the Mediterranean sea, the Dietary Approaches to Stop Hypertension (DASH) diet features a high intake of fruits, vegetables, whole grains (complex carbohydrates), low‐fat dairy products, legumes and nuts, and a low intake of sodium, sweetened beverages, and red processed meat 10, 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary patterns can directly be translated into dietary recommendations to be used in clinical practice 7, 8. Previously, we found that a Mediterranean‐style diet is associated with a lower risk of new‐onset diabetes and all‐cause mortality after renal transplantation 9. In contrast to the Mediterranean diet, which is based on a diet traditionally consumed by the inhabitants of regions surrounding the Mediterranean sea, the Dietary Approaches to Stop Hypertension (DASH) diet features a high intake of fruits, vegetables, whole grains (complex carbohydrates), low‐fat dairy products, legumes and nuts, and a low intake of sodium, sweetened beverages, and red processed meat 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Previously, we found that a Mediterranean-style diet is associated with a lower risk of new-onset diabetes and all-cause mortality after renal transplantation. 9 In contrast to the Mediterranean diet, which is based on a diet traditionally consumed by the inhabitants of regions surrounding the Mediterranean sea, the Dietary Approaches to Stop Hypertension (DASH) diet features a high intake of fruits, vegetables, whole grains (complex carbohydrates), low-fat dairy products, legumes and nuts, and a low intake of sodium, sweetened beverages, and red processed meat. 10,11 Originally, the DASH diet was developed to reduce blood pressure, and considering that hypertension is associated with graft failure [12][13][14] and mortality in RTR, 15 the DASH diet might greatly benefit RTR.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, including KTR with a minimum of 6 months of transplantation, B 12 deficiency prevalence (cut-off < 200 pg/ml) was 14 %. Some authors have evaluated the dietary intake in KTR (48)(49)(50) , but only one study evaluated the intake of B 12 (48) , that was considered adequate in 94 % of the patients. In the present study, we found that a lower percentage of the participants (64 %) presented adequate B 12 intake.…”
Section: Discussionmentioning
confidence: 99%
“…Validation of the FFQ in RTR was assessed as previously reported (Oste et al. ). Dietary data were converted into daily nutrient intake using the Dutch Food Composition Table of 2006 (National Institute for Public Health and the Environment, .)…”
Section: Methodsmentioning
confidence: 99%
“…All FFQs were checked for completeness by a trained researcher, and inconsistent answers were verified with the patients. Validation of the FFQ in RTR was assessed as previously reported (Oste et al 2017). Dietary data were converted into daily nutrient intake using the Dutch Food Composition Table of 2006 (National Institute for Public Health and the Environment, 2013.)…”
Section: Data Collection and Measurementsmentioning
confidence: 99%